Apgar Score and Risk of Cerebral Palsy in Preterm Infants: A Population-Based Cohort Study - Osredkar, Damjan; Verdenik, Ivan; Gergeli, Anja Troha; Gersak, Ksenija; Lucovnik, Miha (Neuropediatrics, 2021)
A low Apgar score is associated with increased risk of cerebral palsy (CP) in term infants, while such association remains controversial in preterm neonates. The objective of this study was to assess association between 5-minute Apgar scores and CP in different subcategories of preterm birth based on gestational age. The Slovenian National Perinatal Information System was used to identify singleton children without congenital malformations live-born at 22 to 37 weeks of gestation between 2002 and 2010. Data were linked to the Slovenian Registry of Cerebral Palsy in children born between 2002 and 2010. CP was diagnosed at a minimum of 5 years of age. Of 11,924 children included, 241 (2.0%) died before discharge and 153 (1.3%) were diagnosed with CP. Five-minute Apgar scores <7 were significantly associated with higher risk of death or CP (compared with scores ≥9) at all preterm gestations. CP alone was associated with Apgar scores <7 only at moderately or late preterm gestation (32–36 weeks) (adjusted relative risk [aRR]: 8.27; 95% confidence interval [CI]: 1.87–36.64 for scores 0–4 and aRR: 4.96; 95% CI 1.89–13.06 for scores 5–6). In conclusion, a low 5-minute Apgar score was associated with combined outcome of neonatal death or CP in all preterm births, while in surviving preterm infants at >32 weeks a low 5-minute Apgar score was associated with CP.
Keywords: Apgar score; cerebral palsy; preterm birth